Hepatocellular carcinoma patient survival is sustained by activation of innate immunity within the tumor microenvironment - Chan, Jasmine Mei Wen (Nanyang Technological University, 2008)
Hepatocellular carcinoma (HCC) is a highly aggressive primary cancer of the liver. In Asia, HCC most commonly develops secondary to viral hepatitis infections. Chronic inflammation has a well-established role in carcinogenesis in HCC. In well established tumours, the immune system has been described to either aid in progression or regression, depending on immune cell type, polarization and function. This retrospective study was aimed at describing the immune microenvironment within HCC and identifying immune mechanisms that are associated with clinical endpoints. Transcriptome analysis on 61 patients indicated that a pro-inflammatory and innate immunity gene signature is associated with longer HCC survival.